2023
DOI: 10.3390/agriculture13091741
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Evapotranspiration of Greenhouse Tomato under Different Irrigation Levels Using a Modified Dual Crop Coefficient Model in Northeast China

Mingze Yao,
Manman Gao,
Jingkuan Wang
et al.

Abstract: Accurate quantification of evapotranspiration (ETc) and its components are critical for enhancing water use efficiency and implementing precision irrigation. A two-year experiment was conducted for greenhouse-grown tomatoes under mulched drip irrigation with three irrigation treatments during 2020–2021 in Northeast China. Three different irrigation treatments were applied by setting upper and lower soil moisture irrigation thresholds (i.e., W1, 65%θFC–75%θFC, W2, 75%θFC–85%θFC, W3, 85%θFC–95%θFC, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Furthermore, the difference in marketable yield values between irrigation levels was statistically significant (p < 0.01). Yao et al [50] reported that it is crucial to accurately determine ETc and its components for attaining efficient irrigation scheduling and enhancing water use efficiency. Water stress causes yield loss because as the soil dries, the soil matrix strongly retains soil water, and the soil water concentration increases [36].…”
Section: Water Consumption and Water Use Efficiency (Wue)mentioning
confidence: 99%
“…Furthermore, the difference in marketable yield values between irrigation levels was statistically significant (p < 0.01). Yao et al [50] reported that it is crucial to accurately determine ETc and its components for attaining efficient irrigation scheduling and enhancing water use efficiency. Water stress causes yield loss because as the soil dries, the soil matrix strongly retains soil water, and the soil water concentration increases [36].…”
Section: Water Consumption and Water Use Efficiency (Wue)mentioning
confidence: 99%